Nintendo and the Blue Ocean Strategy: Designing the Four Actions Matrix - Flores Flores, Adan Jacinto (Mercados y Negocios, 2025)
The purpose of this article is to analyze the strategies adopted by Nintendo within the framework of the four-action matrix of the BOS (i.e., eliminate, reduce, increase, and create). Documentary research was implemented by scrutinizing the scientific bases of information accessible in electronic media (e.g., Web of Science and Scopus). For each of the four actions of the matrix, the following factors were identified: 1. eliminate the expensive face-to-face conferences; 2. reduce the graphic power of the video game console, the budgets, and the deadlines in the development of video games; 3. increase: the brand extension; and 4. create: nostalgic feeling. This study offers valuable lessons and insights for organizational strategists to consider when designing strategies that leverage distinctive characteristics to create competitive advantages that satisfy both established objectives and customer desires and expectations. Furthermore, the work can serve as a reference framework for subsequent empirical research.